"The Jew Usually Left Those Crimes to Esau": The Jewish Responses to Accusations about Jewish Criminality in New York, 1908–1913. Issue 1 (2nd May 2014) - Ribak, Gil
<x content-type="archive" xml:space="preserve">Abstract</x> This article examines how communal activists, leaders, intellectuals, and the Yiddish press understood and reacted to charges regarding purported Jewish criminality, which accusers often linked to the need to curtail immigration to America. The Jewish self-image as a nonviolent people proved to be quite resilient, and one of the ways to reconcile the existence of Jewish criminals with that self-perception was to put the blame on the surrounding (American) influence, or to evoke generalized negative images of gentiles as a foil for applauding Jewish qualities. New York Jews construed their relations with the larger non-Jewish society as a continuation of old-world patterns of Jewish-gentile relations rather than a change or reversal of them. The criminal episodes demonstrated how a cultural net of transnational meanings shaped Jews' understanding and reaction to allegations against them.